A Review of Coronaviruses Associated With Kawasaki Disease: Possible Implications for Pathogenesis of the Multisystem Inflammatory Syndrome Associated With COVID-19. (February 2022) - Shahbaz, Fatima Farrukh; Martins, Russell Seth; Umair, Abdullah; Ukrani, Ronika Devi; Jabeen, Kausar; Sohail, M Rizwan; Khan, Erum
Multisystem Inflammatory Syndrome in Children (MIS-C), representing a new entity in the spectrum of manifestations of COVID-19, bears symptomatic resemblance with Kawasaki Disease (KD). This review explores the possible associations between KD and the human coronaviruses and discusses the pathophysiological similarities between KD and MIS-C and proposes implications for the pathogenesis of MIS-C in COVID-19. Since 2005, when a case-control study demonstrated the association of a strain of human coronavirus with KD, several studies have provided evidence regarding the association of different strains of the human coronaviruses with KD. Thus, the emergence of the KD-like disease MIS-C in COVID-19 may not be an unprecedented phenomenon. KD and MIS-C share a range of similarities in pathophysiology and possibly even genetics. Both share features of a cytokine storm, leading to a systemic inflammatory response and oxidative stress that may cause vasculitis and precipitate multi-organ failure. Moreover, antibody-dependent enhancement, a phenomenon demonstrated in previous coronaviruses, and the possible superantigenic behavior of SARS-CoV-2, possibly may also contribute toward the pathogenesis of MIS-C. Lastly, there is some evidence of complement-mediated microvascular injury in COVID-19, as well as of endotheliitis. Genetics may also represent a possible link between MIS-C and KD, with variations in FcγRII and IL-6 genes potentially increasing susceptibility to both conditions. Early detection and treatment are essential for the management of MIS-C in COVID-19. By highlighting the potential pathophysiological mechanisms that contribute to MIS-C, our review holds important implications for diagnostics, management, and further research of this rare manifestation of COVID-19.